ExtSFR: scalable file recovery framework based on an Ext file system - Lee, Seokjun; Jo, Wooyeon; Eo, Soowoong; Shon, Taeshik (Multimedia Tools and Applications, 2020)
As the technologies based on the Internet of Things, the Cloud, Big Data, and mobile technology have recently become the engine of the next-generation fusion environment, the use of consumer electronics with Linux/Unix-based operating systems which include mobile and embedded operating systems has been gradually increasing. As these technologies are applied in the real world, digital forensics and post-processing techniques in the next-generation environment are required for security/privacy perspective. In this paper, an Ext2/3/4 file system’s file recovery framework which is suitable for the next-generation environment is proposed. Also, Ext4 used from small to large size file systems in recent consumer electronics such as home appliances, mobile devices, home-office devices, entertainment devices, etc. The proposed framework takes the various Ext4 file systems created in the IoT/Cloud/Big Data/mobile environment into account, and it is configured to accommodate not only Ext4 used mainly in the recent environment but also Ext2/3 legacy environment. Additionally, the proposed framework is implemented as a prototype and validated it by comparing it with the existing commercial technologies, showing that the accuracy and efficiency of the prototype of the proposed framework for large file system recovery rates are superior to those of the existing technologies.
Keywords: Commercial technology; Data recovery; Embedded operating systems; Entertainment devices; File systems; Large-file system; Mobile Technology; Post-processing techniques; Consumer electronics; Data recovery; Data security; Digital forensics; File systems